Developments in research on abiotic stress responsive microRNAs of Hevea brasiliensis - Sathik M.B.M; Kuruvilla L (Indian Journal of Plant Physiology, 2017)
Abiotic stress such as drought and low temperature are the major environmental factors that restrict the expansion of Hevea brasiliensis (rubber tree) cultivation to non-traditional regions of India. The H. brasiliensis cultivars, which are proven superior in traditional regions, do not perform well in such regions and hence it is imperative to find/develop stress tolerant cultivars spcifically for these regions. Marker assisted selection for stress tolerance is widely employed to minimize time required to develop such cultivars with desired traits. In this review, developments in abiotic stress responsive gene expression studies in Hevea with special reference to miRNA research are discussed. The recent researches in this field have revealed the nature of abiotic stress responsive miRNAs and their possible role on their corresponding target genes. These attempts indicate the possibility of employing specific stress tolerance associated miRNAs in the crop improvement programmes by the breeders to identify or develop drought/cold-tolerant cultivars of H. brasiliensis.
Source Year: 2017
Keywords: Abiotic stress; Cold stress; Drought; Gene expression; Hevea brasiliensis; MicroRNA